2012
DOI: 10.1016/j.jnci.2012.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study between the effect of methotrexate and valproic acid on solid Ehrlich tumour

Abstract: MTX has more antitumour effect than VPA against SEC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…It is known that the invasiveness generated by surgical orthotopic transplantation signifi cantly increases the likelihood of metastases [62][63][64] caused by mechanical injuries that may lead even to an increased expression of genes promoting metastasis of breast cancer to the lungs. days [74,75] after ectopic transplantation. In this regard, the earlier clinical detection of the tumor is interesting because it is more suitable for the study of new therapies.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that the invasiveness generated by surgical orthotopic transplantation signifi cantly increases the likelihood of metastases [62][63][64] caused by mechanical injuries that may lead even to an increased expression of genes promoting metastasis of breast cancer to the lungs. days [74,75] after ectopic transplantation. In this regard, the earlier clinical detection of the tumor is interesting because it is more suitable for the study of new therapies.…”
Section: Discussionmentioning
confidence: 99%
“…the resistance of cancer cells to TNF-α induced death based on the fact that TNF-α induced survival signals such as nuclear factor-κB (NF-κB) that blunt the apoptotic pathway and activated the survival pathway ( WAJANT et al, 2003). In a concurrent study, Abdel-Rahman and Kabel (2012) noted that, immune-staining of TNF-α and Bcl-2 showed over expression in the group of mice bearing tumour while down expression of Bax was observed in the same group. Meanwhile, Sun et al (2010) reported that cancer cells down-regulate TIMP and produce extracellular MMP-inducer, a cell surface glycoprotein, which directly stimulates fibroblasts to produce MMP-1, 2, 3, 9 and 14.…”
Section: Discussionmentioning
confidence: 99%
“…Cancer is one of the major causes of death, the general conventional treatment and standard care for clinical oncology remains surgery followed by radiation and/or systemic chemotherapy (ABD EL-WAHAB; FOUDA, 2009). Apoptosis is a mode of cell death used by multicellular organisms to remove cells in diverse physiological and pathological settings (BHATTACHARYYA et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The tumor growth was measured regularly using Vernier calipers and represented in terms of tumor size. The tumor size was estimated using the following formula: Tumor size (mm 3 ) = 4 π ( A /2) 2 ( B /2), where A is the minor tumor axis; B is the major tumor axis, and π equals to 3.14 [14] . The mean tumor size with the corresponding standard error was calculated in each experimental group.…”
Section: Methodsmentioning
confidence: 99%